The Methodist Church in Poland in reality of liquidation policy. Operation "Moda" (1949-1955) - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to analyze the determinants and other conditions of the religious policy of the Polish state towards the Methodist Church in the Stalinist period. The author took into account conceptual, programmatic, executive and operational activities undertaken by a complex subject of power, formed by three structures: party, administrative and special services.
Keywords: religious policy; liquidation policy; regulatory policy; special services; Methodism; Methodist Church